2021
DOI: 10.1371/journal.pntd.0009426
|View full text |Cite
|
Sign up to set email alerts
|

Past and present of cystic echinococcosis in Bolivia

Abstract: Viable eggs of the canine intestinal tapeworm Echinococcus granulosus sensu lato (s.l.) infect various intermediate hosts causing cystic echinococcosis (CE). Furthermore, CE represents a serious zoonosis causing a significant global burden of disease. CE is highly endemic in South America, including Argentina, Brazil, Chile, Uruguay, and Peru. For Bolivia, no official data concerning the incidence in humans or the number of livestock and dogs infected are available. However, it is well known that CE occurs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previously, Cucher et al (2016) reviewed the diversity of the CE in domestic intermediate hosts and human cases from South America and showed that E. granulosus s.s., E. ortleppi and G6/7 cluster of E. canadensis are prevailed among examined livestock, particularly from Argentina, Brazil, Uruguay and Peru (Cucher et al, 2016). Likewise, studies from Bolivia have reported considerable prevalence in slaughtered livestock (Ali et al, 2021). Due to such a great diversity of CE among livestock in South America, it is assumed that unchallenging access to the offal of slaughtered animals containing fertile cysts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Cucher et al (2016) reviewed the diversity of the CE in domestic intermediate hosts and human cases from South America and showed that E. granulosus s.s., E. ortleppi and G6/7 cluster of E. canadensis are prevailed among examined livestock, particularly from Argentina, Brazil, Uruguay and Peru (Cucher et al, 2016). Likewise, studies from Bolivia have reported considerable prevalence in slaughtered livestock (Ali et al, 2021). Due to such a great diversity of CE among livestock in South America, it is assumed that unchallenging access to the offal of slaughtered animals containing fertile cysts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Following Table 1 , where the pooled prevalence across Asia was 0.0177, numerous studies found substantially higher rates of CE in certain regions, such as rural Mongolia (2.0% to 13.1%) [ 88 ], the Fars province of Southern Iran (8.73%) [ 89 ], and rural Zahedan, Iran (4%) [ 90 ]. The same holds true for South America, where the pooled prevalence was 0.0342, but higher prevalence rates were found in parts of Potos Department, Bolivia (4,3%) [ 91 , 92 ], and La Rioja Province, Argentina [ 93 ], emphasizing the need for more effective surveillance and control methods worldwide.…”
Section: Discussionmentioning
confidence: 86%